2022
DOI: 10.3389/fnut.2022.781860
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Fully Automatic Deep Learning-Based Method for the Measurement of Psoas Muscle Area

Abstract: BackgroundManual muscle mass assessment based on Computed Tomography (CT) scans is recognized as a good marker for malnutrition, sarcopenia, and adverse outcomes. However, manual muscle mass analysis is cumbersome and time consuming. An accurate fully automated method is needed. In this study, we evaluate if manual psoas annotation can be substituted by a fully automatic deep learning-based method.MethodsThis study included a cohort of 583 patients with severe aortic valve stenosis planned to undergo Transcath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…that this automatic tool is reliable and could substitute manual measurement of body composition. 28 Additionally, for almost all cancer patients, a CT scan is made before treatment. If the L3 slice is not incorporated in the scanned area, for example for head and neck cancer patients, the skeletal muscle area at the C3 slice could be used to calculate the skeletal muscle area at the L3 slice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…that this automatic tool is reliable and could substitute manual measurement of body composition. 28 Additionally, for almost all cancer patients, a CT scan is made before treatment. If the L3 slice is not incorporated in the scanned area, for example for head and neck cancer patients, the skeletal muscle area at the C3 slice could be used to calculate the skeletal muscle area at the L3 slice.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, Quantib Body Composition is the only available software for automatic body composition analysis. Van Erck et al concluded that this automatic tool is reliable and could substitute manual measurement of body composition 28 . Additionally, for almost all cancer patients, a CT scan is made before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The PET-CT scans were made over a nine-year period and in nine different hospitals, which means there was natural variation in scanner vendor, model, tube current, voxel spacing, slice thickness and radiation dose. We used Quantib Body Composition version 0.2.1 (Quantib BV, Rotterdam, The Netherlands) for automated muscle measurements [ 22 ]. The CT scans were first resampled to a uniform slice thickness of 5mm.…”
Section: Methodsmentioning
confidence: 99%
“…Metrics were obtained using Quantib Body Composition version 0.2.1, a dedicated deep learning segmentation algorithm that has proven to achieve high correspondence to manual segmentations in previous studies [18][19][20]. First, all baseline CT scans were resampled to a slice thickness of 5mm.…”
Section: Ct Body Composition Metrics Extractionmentioning
confidence: 99%